Introduction to space law - Masson-Zwaan, Tanja L. (Wolters Kluwer Kluwer Law International, 2019)
Introduction to Space Law' is a completely revised edition since the previous version of 2008, providing a concise and structured analysis of legal aspects of both traditional and more recent space activities. The relevance and substance of space law as a branch of public international law continues to expand. The fourth edition of this long-time classic in the field of space law has been substantially rewritten to reflect new developments in space law and technology of the past ten years, but the main structure of the original book has been preserved. This updated text includes new or expanded material on the proliferation of non-state and commercial entities as space actors, the appearance of innovations in space technology, the evolving international law of satellite telecommunications in a networked world, and the adoption of national laws and international soft law mechanisms that complement the international treaty regime.